Asymmetric credit growth and current account imbalances in the euro area - Robert Unger (Deutsche Bundesbank, 2015)
The euro area crisis is often linked to the emergence of current account imbalances. As most of the deficit countries experienced pronounced credit booms at the same time that these imbalances were building up, this paper investigates the link between domestic credit developments and the current account balance, distinguishing between a credit pull and a credit push factor. The pull factor captures flows of bank loans to the domestic non-financial private sector. An increase in these flows is expected to lead to higher domestic demand and a deterioration of the current account. The push factor measures flows of claims of domestic banks on debtors in other euro-area countries, and an increase is expected to lead to higher external demand and an improvement in the current account. Using a panel error correction specification, the estimation results confirm that the pull factor is a significant determinant of the current account, whereas the results for the push factor are less clear-cut. The paper also shows that variations in the flows of bank loans to the non-financial private sector (i.e. the pull factor) - together with changes in competitiveness - constituted the most important factor driving the build-up of current account imbalances in the deficit countries. Accordingly, impeding an increase in private sector indebtedness seems to be a promising way to dampen the formation of unsustainable current account imbalances.
Keywords: E5; F32; F45; 330; banks; credit growth; current account imbalances; euro area; Bank; Kreditgeschäft; Leistungsbilanz; Eurozone